Effect of the Extensive Use of Granites as Countertops in Luxury Buildings on the Indoor Radon Concentration and the Potential Risk to Occupants - Mohammed S. Tayeb,; Abdulraheem A. Kinsara, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Radon concentration has been measured inside the new buildings of King Abdulaziz University to study the effect of the extensive use of granites as countertops on the indoor radon concentration. A set of indoor and outdoor measurements has been conducted using radon measurement instruments. For comparison, indoor radon concentration was also measured in the older buildings, where granite countertops were in use at only a few sites near the main entrances. The obtained results indicate that the average indoor radon concentrations were 8.8 ± 4.8 and 11.2 ± 4.9 Bq/m3 in the old and new buildings, respectively. The average outdoor concentration was about 4.4 Bq/m3. These values are lower than the global average values. The average annual eff ective dose due to indoor radon was calculated for the general public and for the occupants of the new buildings. Risk estimates have been done based on the average radon concentration values. The average annual effective dose for the public due to radon inhalation was estimated to be 0.264 mSv, and for the occupants of the new buildings to be 0.280 mSv. The associated risk of lung cancer mortality to inhabitants due to lifetime radon inhalation is estimated to be 102.9x10-5 for the public and 109.5x10-5 for the occupants of the new buildings.